2013
DOI: 10.1007/s12529-013-9370-6
|View full text |Cite
|
Sign up to set email alerts
|

Negative Affectivity, Emotion Regulation, and Coping in Migraine and Probable Migraine: A New Zealand Case–Control Study

Abstract: A personality profile characterised by moderate levels of negative emotion and irritability together with failures in inhibitory self-regulation may be associated with an increased risk of strict and probable migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
(61 reference statements)
2
9
2
9
Order By: Relevance
“…In addition, openness has been found to be associated with lesser physiological reactivity and higher physiological adaptation, measured by hart rate, blood pressure, and respiratory rhythm changes, to recurrent social evaluative stress, suggesting that openness might be a protective factor against harmful effects of stress (38). Regarding migraine, in line with our results, migraineurs with higher openness are also more flexible and creative in their approach to managing their condition which in turn reduces the impact of migraine on their daily life, which is also reflected in less impaired function in migraineurs with higher openness (39). This effect is especially important in the comorbidity of depression and migraine as migraine and depression have already been reported to have a peculiar relationship reflected by their high comorbidity.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, openness has been found to be associated with lesser physiological reactivity and higher physiological adaptation, measured by hart rate, blood pressure, and respiratory rhythm changes, to recurrent social evaluative stress, suggesting that openness might be a protective factor against harmful effects of stress (38). Regarding migraine, in line with our results, migraineurs with higher openness are also more flexible and creative in their approach to managing their condition which in turn reduces the impact of migraine on their daily life, which is also reflected in less impaired function in migraineurs with higher openness (39). This effect is especially important in the comorbidity of depression and migraine as migraine and depression have already been reported to have a peculiar relationship reflected by their high comorbidity.…”
Section: Discussionsupporting
confidence: 87%
“…Migraines are associated with a wide range of medical and psychiatric comorbidities 41 ; for example, migraines increase anxiety levels 15 , and migraine disability has been correlated with depression scores and stress scores 16 . Additionally, a personality profile characterized by moderate levels of negative emotion and irritability, together with failures in inhibitory self-regulation, could be induced an increased risk of strict and probable migraines 42 . The literature has suggested that migraines are associated with negative emotion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies addressing psychological factors have focused mainly on pain-related variables such as pain coping (Biagianti, Grazzi, Usai, & Gambini, 2014 ), pain catastrophising (Goli, Asghari, & Moradi, 2014 ) and pain acceptance (Chiros & O’Brien, 2011 ). Since stress is named most frequently as a potential trigger of attacks (Hashizume et al, 2008 ; Houle et al, 2012 ), and migraine is considered to be characterised by a maladaptive stress response (Borsook, Maleki, Becerra, & McEwen, 2012 ), general coping strategies have been also addressed by studies (Chan & Consedine, 2014 ; Radat et al, 2008 ). However, these studies have not assessed individual differences in psychological functioning that are reliably associated with psychopathologies and can worsen stress response.…”
Section: Introductionmentioning
confidence: 99%